2001
DOI: 10.1590/s0100-879x2001000500006
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of laminin with the amyloid ß peptide: Implications for Alzheimer's disease

Abstract: Extensive neuronal cell loss is observed in Alzheimers disease. Laminin immunoreactivity colocalizes with senile plaques, the characteristic extracellular histopathological lesions of Alzheimer brain, which consist of the amyloid ß (Aß) peptide polymerized into amyloid fibrils. These lesions have neurotoxic effects and have been proposed to be a main cause of neurodegeneration. In order to understand the pathological significance of the interaction between laminin and amyloid, we investigated the effect of lam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…Over-expression of the ␥1 laminin in reactive astrocytes of the diseased human brain was reported in 1992 (Murtomäki et al, 1992) whereas the presence of additional matrix proteins, such as fibronectin, remains controversial (Koike et al, 1988;Howard and Pilkington, 1990). In recent years, new insight has emerged in understanding the expression of laminin-1 in the Alzheimer brain tissue (Morgan and Inestrosa, 2001). Laminin-1 and its ␣1-chain have been shown to prevent neurotoxicity of the amyloid-␤-peptide (Drouet et al, 1999), to inhibit fibrillogenesis of the amyloid-␤-peptide (Bronfman et al, 1996b;Monji et al, 1998a,b;Castillo et al, 2000) and to modulate biogenesis of the APP (Mönning et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over-expression of the ␥1 laminin in reactive astrocytes of the diseased human brain was reported in 1992 (Murtomäki et al, 1992) whereas the presence of additional matrix proteins, such as fibronectin, remains controversial (Koike et al, 1988;Howard and Pilkington, 1990). In recent years, new insight has emerged in understanding the expression of laminin-1 in the Alzheimer brain tissue (Morgan and Inestrosa, 2001). Laminin-1 and its ␣1-chain have been shown to prevent neurotoxicity of the amyloid-␤-peptide (Drouet et al, 1999), to inhibit fibrillogenesis of the amyloid-␤-peptide (Bronfman et al, 1996b;Monji et al, 1998a,b;Castillo et al, 2000) and to modulate biogenesis of the APP (Mönning et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Although no laminins have been considered as a cause for the disease, they appear to participate, like a number of other proteins, in the pathophysiology of neuronal death by regulating fibrillogenesis of the amyloid-␤-peptide (Castano et al, 1995;Bronfman et al, 1996Bronfman et al, , 1997Castillo et al, 1997;Monji et al, 1998aMonji et al, ,b, 2000Cotman et al, 2000;Morgan and Inestrosa, 2001;Nilsson et al, 2001). Thus, laminins may interact with proteins genetically linked to Alzheimer disease (such as APP and presenilins) in ways important for development of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[38][39][40] In many scaffold-based cultures, the scaffold introduces foreign ECM to the microenvironment, which can potentially modify cell behavior and mask disease-related changes in the culture model. In the spheroids of this work, the cells produced all of the ECM.…”
Section: Versatile Culturementioning
confidence: 99%
“…Among these are laminin (Bronfman et al 1996; Drouet et al 1999; Monji et al 1999; Morgan et al 2002) and gelsolin (Chauhan et al 1999, 2008; Ray et al 2000; Qiao et al 2005), which have been shown to bind and form complexes with the Aβ peptide. Laminin is a major basement membrane protein shown to inhibit Aβ fibril formation and to disaggregate preformed Aβ fibrils (Monji et al 1999; Morgan and Inestrosa 2001; Morgan et al 2002). Gelsolin is found both as an intracellular protein (Tanaka and Sobue 1994; Ji et al 2008), which is able to modulate actin assembly and disassembly (Janmey et al 1985; Howard et al 1990), and as a secreted plasma and CSF protein (Kwiatkowski et al 1988; Paunio 1994; Kulakowska et al 2008).…”
Section: Introductionmentioning
confidence: 99%